GRASCCO - The First Publicly Shareable, Multiply-Alienated German Clinical Text Corpus. - Modersohn, L.; Schulz, S.; Lohr, C.; Hahn, U. (Stud Health Technol Inform, 2022)
We describe the creation of GRASCCO, a novel German-language corpus composed of some 60 clinical documents with more than.43,000 tokens. GRASCCO is a synthetic corpus resulting from a series of alienation steps to obfuscate privacy-sensitive information contained in real clinical documents, the true origin of all GRASCCO texts. Therefore, it is publicly shareable without any legal restrictions We also explore whether this corpus still represents common clinical language use by comparison with a real (non-shareable) clinical corpus we developed as a contribution to the Medical Informatics Initiative in Germany (MII) within the SMITH consortium. We find evidence that such a claim can indeed be made.
Keywords: Germany; *Language; *Natural Language Processing